2015
DOI: 10.3174/ajnr.a4220
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary-Targeted Dynamic Contrast-Enhanced Multisection CT for Detecting MR Imaging–Occult Functional Pituitary Microadenoma

Abstract: BACKGROUND AND PURPOSE:Although resection of a tumor by trans-sphenoidal surgery is considered the criterion standard for successful surgical treatment of functional pituitary microadenoma, MR imaging occasionally fails to visualize and identify the tumor and supplementary imaging modalities are necessary. We tested the possibility of dynamic contrast-enhanced multisection CT of the pituitary gland accompanying image reconstruction of contrast agent dynamics to identify the localizations of microadenomas and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 13 publications
0
8
0
2
Order By: Relevance
“…In addition, our analysis did not use advanced MRI techniques, including dynamic contrast-enhancement (DCE)-MRI of the sellar fossa. A recent study [ 28 ] reported that DCE-MRI helps to localize and characterize pituitary lesions; therefore, a future study should use the homogenous pulse sequence to characterize the signal intensity and dynamic pattern of contrast enhancement. Fourth, although our diagnostic model was tested on an independent data set, the patients were recruited from the same institution; therefore, the study is somewhat limited in terms of generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our analysis did not use advanced MRI techniques, including dynamic contrast-enhancement (DCE)-MRI of the sellar fossa. A recent study [ 28 ] reported that DCE-MRI helps to localize and characterize pituitary lesions; therefore, a future study should use the homogenous pulse sequence to characterize the signal intensity and dynamic pattern of contrast enhancement. Fourth, although our diagnostic model was tested on an independent data set, the patients were recruited from the same institution; therefore, the study is somewhat limited in terms of generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…More advanced technology like multiple slice CT scanners and high field MRI scanners may well give more positive results for the detection of pituitary adenomas in dogs. In human medicine the preferred diagnostic imaging technique to diagnose a pituitary adenoma is high-field MRI (De Rotte et al, 2016) whereas CT is performed in cases where MRI failed in the identification of the tumor (Kinoshita et al, 2015). MRI is also used to guide the surgeon in the preoperative planning of the endoscopic transsphenoidal surgery and can also be used intraoperatively but this requires expensive adaptations to the surgical room which are not feasible in veterinary medicine at this moment.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic contrast-enhanced multisection computerized tomography combined with image reconstruction of the contrastenhanced dynamic imaging could detect MR imaging-occult pituitary microadenomas. 11,12 Golden-angle radial sparse parallel (GRASP) is a rapid MRI sequence which could have the potential to increase F I G U R E 1 Picocorticotropinoma and small pituitary gland. The adenoma is hyperintense on T2W images (A), nonenhanced on T1W gadolinium enhanced images (B) and enhanced on 1 h late delayed images (C)…”
Section: Detecting An Intrasellar Abnormalitymentioning
confidence: 99%
“…Pituitary adenoma enhancement can be more pronounced and then more visible on FLAIR (fluid‐attenuated inversion recovery) if compared with the SE T1W enhanced sequence 10 (Figure 7). Dynamic contrast‐enhanced multisection computerized tomography combined with image reconstruction of the contrast‐enhanced dynamic imaging could detect MR imaging‐occult pituitary microadenomas 11,12 . Golden‐angle radial sparse parallel (GRASP) is a rapid MRI sequence which could have the potential to increase sensitivity through higher temporal resolution if compared with conventional dynamic MRI sequence 13 (Figure 8).…”
Section: Detecting An Intrasellar Abnormalitymentioning
confidence: 99%